Trade diversion and trade creation the case of Turkey establishing customs union with the European Union - Ulusoy, Veysel; Sözen, Ahmet (EuroJournals, Inc., 2008)
This paper explores the logical and empirical determinants of the Custom Union membership of Turkey with European Union effective in 1996 and reflects on the potential of trade creation and trade diversion effects of this membership. The paper applies a gravity model to estimate such trade effects. The gravity model offers a good application of the spatial interaction method. Results show that trade has been diverted by this membership for the first five years. © EuroJournals Publishing, Inc. 2008.